ANTI-MONEY LAUNDERING AS INTERNATIONAL STANDARDS AND THE ISSUE OF STATE SOVEREIGNTY - Amrani, Hanafi (UI Scholars Hub, 2015)
It has been recognized that the anti-money laundering regime comprises of preventive and repressive measures. Regarding the preventive measures, the Financial Action Task Force (FATF) on Money Laundering issued the Forty Recommendations which are regarded as international standards in preventing and controlling money laundering activities. These standards are generally viewed as ‘soft law’ and have levels of intervention in legislative, financial, and law enforcement of members and non-member countries of the FATF. However, the rule-making as well as the implementation and enforcement strategy of these standards are not involved and approved by non-member countries. This article argues that this policy is contrary to the principle of state sovereignty and regarded as one of state interventions in the domestic affairs of another state. This article seeks to draw the Forty Recommendations as international standards and examines the creation and implementation of these standards from the standpoint of state sovereignty by focusing exclusively on the principle of sovereign equality and non-interference.